Przyczynek do dyskusji nad pojęciem systemu rządów - Michalczuk-Wlizło, Marta; Żmigrodzki, Radosław (Wydawnictwo Naukowe WNPiD UAM, 2012)
The considerations presented in this paper are focused on the issue of governmental systems. The authors try to outline the main problems and dilemmas as concerns its definitions. They point to the normative elements of governmental systems and discuss the issue of efficiency, because every governmental system is defined by formal (established in legal regulations) as well as the actual, or real, relationship between the legislative and executive power. While the interdependence of legislative and executive power is the main focus here, judicial power is also referred to. In order to comprehensively present and characterize a given governmental system it is advisable to account for the legal and constitutional aspects, as well as practical ones. The concept of a political regime or a political system in relation to governmental systems is also discussed, and criteria for the analysis of the interdependence of individual powers in the state are indicated.
A Contribution to the Discussion on the Concept of Governmental Systems